2020
DOI: 10.18805/lr-566
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Planting Distance and Seed Rate on the Growth and Yield of Egusi Melon (Citrullus colocynthis)

Abstract: Background: Egusi melon production is declining, even though the crop plays a significant role in the well-being of farmers. Few farmers that grow the crop do not allow adequate spacing and seed rate which compels the crop to produce flourishing vegetative parts without producing many fruits. The study was therefore, aimed at determining the effect of planting distance and seed rate on the growth and yield of egusi melon. Methods: A split-plot design which was replicated thrice was adopted to carry out the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Beech and Leach, (1989) showed that the number of plants per unit area influences plant size, yield components and eventually the seed yield in chickpea. Furthermore, plant spacing in the field is also very important Effect of Row Spacing and Seed Rate on Ascochyta Blight Severity and Yield of Chickpea (Cicer arietinum L.) in Tunisia to facilitate aeration and light penetration into plant canopy for optimizing rate of photosynthesis as confirmed by Ugwuoke et al, (2021). Optimum spacing can ensure proper growth of the aerial and underground parts of the plant through efficient utilization of solar radiation, nutrients, water, land as well as air spaces and thereforecontribute to the increase of chickpea yield as confirmed by Malik and Singh, (1996).…”
Section: Introductionmentioning
confidence: 95%
“…Beech and Leach, (1989) showed that the number of plants per unit area influences plant size, yield components and eventually the seed yield in chickpea. Furthermore, plant spacing in the field is also very important Effect of Row Spacing and Seed Rate on Ascochyta Blight Severity and Yield of Chickpea (Cicer arietinum L.) in Tunisia to facilitate aeration and light penetration into plant canopy for optimizing rate of photosynthesis as confirmed by Ugwuoke et al, (2021). Optimum spacing can ensure proper growth of the aerial and underground parts of the plant through efficient utilization of solar radiation, nutrients, water, land as well as air spaces and thereforecontribute to the increase of chickpea yield as confirmed by Malik and Singh, (1996).…”
Section: Introductionmentioning
confidence: 95%
“…The development of integrated disease management options (application of fungicides, crop rotation, use of resistant varieties, sowing date, row spacing and seeding rate) considerably reduces Ascochyta blight infection and are crucial for it's successful control (Ahmed et al, 2016). Furthermore, plant spacing in the field facilitate aeration and light penetration into plant canopy and optimize rate of photosynthesis as confirmed by Ugwuoke et al (2021). Optimum spacing can ensure proper growth of the aerial and underground parts of the plant through efficient utilization of solar radiation, nutrients, water, land as well as air spaces and therefore contribute to the increased yield as confirmed by Malik and Singh, (1996).…”
Section: Introductionmentioning
confidence: 95%
“…In addition to varietal selection, research should be directed more towards the development of appropriate cultivation techniques for increasing lentil Selection of Lentil (Lens culunaris L.) Lines Grown at Different Sowing Dates for Their Precocity and Their Agronomic... yields, especially the date and density of sowing. Results of Sen et al (2016) and Ugwuoke et al (2021) showed that cultural practices in particular the sowing date and dose and planting distance and seed rate are among the parameters that affect the growth and yield of plants. Matthews and Caffery (2011), show that an optimum sowing date can maximize yield potential and minimize disease levels.…”
Section: Introductionmentioning
confidence: 99%